(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Mathematical modeling has become one of the primary methods in modern chemical production. By using various mathematical computation techniques to simulate complex workflows and systems, and analyzing the production process, mathematical modeling helps optimize production efficiency, improve product quality, and enhance the competitiveness and profitability of enterprises. This article analyzes the basic concepts and roles of mathematical modeling in chemical production, including simulation and modeling. It is hoped that the introduction provided in this article can serve as a reference for chemical enterprises.